2004
DOI: 10.1152/jn.00307.2004
|View full text |Cite
|
Sign up to set email alerts
|

A-Current Expression is Regulated by Activity but not by Target Tissues in Developing Lumbar Motoneurons of the Chick Embryo

Abstract: Casavant, Reema H., Costa M. Colbert, and Stuart E. Dryer. A-current expression is regulated by activity but not by target tissues in developing lumbar motoneurons of the chick embryo. J Neurophysiol 92: 2644 -2651, 2004. First published May 26, 2004 10.1152/ jn.00307.2004. The functional expression of A-type K ϩ channels (I A ) was examined in chick lumbar motoneurons (LMNs) at embryonic days 6 and 11 (E6 and E11). We observed a threefold increase in I A density between E6 and E11 in spinal cord slices and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 55 publications
4
11
0
Order By: Relevance
“…Previous studies of vertebrate central synapses have shown homeostatic increases in sodium channel currents (8,20), reductions in Ca 2ϩ -activated potassium currents (16,20), and reductions in the density and inactivation kinetics of transient potassium channels (14) after TTX-induced activity block. We have blocked GABA A transmission and see comparable results to these previous studies that block activity, suggesting a similar process has been triggered.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies of vertebrate central synapses have shown homeostatic increases in sodium channel currents (8,20), reductions in Ca 2ϩ -activated potassium currents (16,20), and reductions in the density and inactivation kinetics of transient potassium channels (14) after TTX-induced activity block. We have blocked GABA A transmission and see comparable results to these previous studies that block activity, suggesting a similar process has been triggered.…”
Section: Discussionmentioning
confidence: 95%
“…SNA is produced by hyperexcitable, recurrently connected circuits in which both GABA and glutamate are excitatory. In the developing spinal cord, SNA has been shown to be important for various aspects of limb (13) and motoneuron (14)(15)(16) development. We have shown recently that when SNA was reduced for 48 h in vivo, compensatory increases in AMPA and GABA A quantal amplitude were triggered, suggesting that homeostatic synaptic plasticity contributed to the maintenance of SNA (9).…”
mentioning
confidence: 99%
“…Homeostatic changes in intrinsic cellular excitability following reductions in spiking activity have been observed for many years and likely play a significant role in recovering or maintaining network activity levels following perturbations (Turrigiano et al, 1994; Thoby-Brisson and Simmers, 1998; Desai et al, 1999; Marder and Prinz, 2002; Karmarkar and Buonomano, 2006; Marder and Goaillard, 2006; Khorkova and Golowasch, 2007) including the chick embryo (Martin-Caraballo and Dryer, 2002; Casavant et al, 2004). Several different channels appear to contribute to the compensatory changes in cellular excitability including transient and calcium-activated potassium channels (I A and I K(Ca) , respectively), the hyperpolarization activated cationic conductance (I H ), and voltage gated sodium channels (I Na ).…”
Section: Cellular Excitability Is Responsible For the Initial Recovermentioning
confidence: 99%
“…For example, inhibition of GABAergic neurotransmission prevents motor axonal guidance [11]. Similarly, GABA-driven network activity regulates the electrical differentiation of spinal motoneurons, including Ca 2+ -dependent and A-type K + channel expression [12,13]. Little is known regarding the role of GABA-mediated activity in regulating the morphological maturation of spinal neurons.…”
Section: Introductionmentioning
confidence: 99%